"Coil mainly" policy in management of intracranial ACoA aneurysms: single-centre experience with the systematic review of literature and meta-analysis - Steklacova, Anna; Bradac, Ondrej; de Lacy, Patricia; Lacman, Jiri; Charvat, Frantisek; Benes, Vladimir (Neurosurgical review, 2018)
Endovascular techniques are still expanding in their capability by introducing novel technologies. Nevertheless, anterior communicating artery (ACoA) remains the region with high propensity for aneurysm (AN) re-growth after endovascular intervention. The purpose of this study is to highlight the ongoing importance for microsurgical treatment. The authors conducted a single-institution retrospective study of ACoA AN treatment between January 2000 and December 2016 maintaining "coil mainly" policy. The results are supplied with a systematic review of the literature. A total of n = 398 ACoA ANs were treated in n = 398 consecutive patients (207 females, 191 males). Microsurgical treatment was performed for 79 AN patients (54 ruptured, 25 unruptured), and 319 AN patients (250 ruptured, 69 unruptured) underwent coiling procedure. Treatment-related morbidity and mortality (MM) for unruptured ANs was 0% in the microsurgical and 1.5% in the endovascular group (p = 1.000). The percentage of patients with none or minor permanent deficits after subarachnoid hemorrhage was 74% in the microsurgical and 70% in the endovascular group (p = 0.693). The re-treatment rate was 3.8% in microsurgical group and 9.2% in endovascular group (p = 0.883). A literature review identified 39 studies concerning ACoA AN treatment. Clinical results of both modalities were comparable, with microsurgery being superior regarding radiological outcomes. This study demonstrates that both treatment techniques bring comparable clinical benefit to the patient. Microsurgery seemed superior regarding radiological outcomes. The decision about the treatment strategy should be made by a multi-disciplinary team consisting of specialists from both teams, bearing in mind the higher occlusion rate and longevity of the surgical treatment.
Keywords: arteria cerebri anterior; dospělí; Endovascular Procedures; Female; endovaskulární výkony; Adult; výsledek terapie; ženské pohlaví; cévní protézy; lidé; Blood Vessel Prosthesis; Intracranial Aneurysm; Neurosurgical Procedures; Treatment Outcome; neurochirurgické výkony; Reoperation; Breast Implantation; Humans; reoperace; intrakraniální aneurysma; Male; Aged; implantace prsní náhrady; Cerebral Revascularization; lidé středního věku; senioři; mužské pohlaví; Anterior Cerebral Artery; Middle Aged; revaskularizace mozku